Abundance of fluoride and its source in drinking water of Kheshki and surrounding area, district Nowshera, N.W.F.P., Pakistan - Danishwar, Shahab; Shah, Mohammad Tahir; Majid, Mohammad (Journal of Himalayan Earth Sciences, 1995)
Fluoride, if present in minute amount in human body, is beneficial for the growth of bones and teeth. Its excess is, however, very harmful and usually causes skeletal fluorosis. Few cases of skeletal fluorosis are reported in Kheshki and surrounding areas in N. W. F. P. The drinking water of study area has been, therefore, analyzed for the fluoride contents. It is noticed that this water has high concentration of fluoride. The source of fluoride enhancement in the drinking water of the area needs to be unraveled. For this purpose, the water of Kabul River, rocks of Nowshera Formation and the lacustrine and soil samples of the area have been analyzed for fluoride. These media show elevated amounts of fluoride. The study suggests that in the lacustrine and soil deposits of the Kheshki and surrounding area the detrital minerals which accommodate fluoride in their structure, are the main contributors of fluoride to the drinking water.